Determination of Toxic Metals in Indian Smokeless Tobacco Products - Dhanashri Dhaware; Aditi Deshpande; R. N. Khandekar; Rohini Chowgule (The Scientific World Journal)
This study targets the lesser-known ingredients of smokeless tobacco products, i.e., the toxic metals, in Indian brands. The metals selected in the study included lead (Pb), cadmium (Cd), arsenic (As), copper (Cu), mercury (Hg), and selenium (Se). The differential pulse anodic stripping voltammetry (DPASV) technique was used for estimating the metals Pb, Cd, and Cu; square wave voltammetry for As; and the cold vapor atomic absorption technique for Hg. The resulting levels of the metals were compared to the daily consumption of the smokeless tobacco products. It was observed that almost 30% of gutkha brand samples exceeded the permissible levels of metals Pb and Cu, when compared to the provisional tolerable intake limits determined by the FAO/WHO. The reliability of data was assured by analyzing standard reference materials.